Relationship between body mass index and adiposity in prepubertal children: ethnic and geographic comparisons between New York City and Jinan City (China) - Navder, Khursheed P.; He, Qing; Zhang, Xiaojing; He, Suyuan; Gong, Luxia; Sun, Yungao; Deckelbaum, Richard J.; Thornton, John; Gallagher, Dympna (Journal of applied physiology (1985), 2009)
Body mass index (BMI) is often used as a surrogate estimate of percent body fat in epidemiological studies. This study tested the hypothesis that BMI is representative of body fatness independent of age, sex, ethnicity, and geographic location in prepubertal children. The study sample included a total of 605 prepubertal children (275 girls and 330 boys) of which 247 were Chinese from Jinan, Shandong, Mainland China, and 358 children were from various ethnic backgrounds in New York City (NYC): 121 Caucasians, 94 African Americans, and 143 Asians (Chinese and Korean). In this cross-sectional study, dual energy X-ray absorptiometry was used to quantify total body fat (TBF) and percent body fat (PBF). Prepubertal status was assessed by the criteria of Tanner. Multiple regression models were developed with TBF and PBF as the dependent variables and BMI, age, sex, and ethnicity as independent variables. Multiple regression analysis showed that BMI alone explained 85% and 69% of between-subject variance for TBF and PBF, respectively. Sex was a significant contributor to the models ( P < 0.001) with girls having higher TBF and PBF than boys. Ethnicity and geographic location were significant contributors to the model ( P < 0.0001) with Asians (Jinan and NYC Asians) having higher PBF than all non-Asian groups ( P < 0.0001), and Jinan Asians having higher TBF and PBF than NYC-Asians. Among prepubertal children, for the same BMI, Asians have significantly higher PBF compared with African Americans and Caucasians. Caution is warranted when applying BMI across sex and ethnic prepubertal groups.